(untitled) (International Journal of Gender, Science and Technology, 2015)
Social Science research on science careers tends to focus on gender as the primary mechanism affecting which people enter and succeed in science. Despite the often narrow focus on gender, the demographic composition of many science fields in the US has changed considerably as the US workforce incorporated more women, people of color, and non-US born workers following important legal changes in the 1960s. Using data from the Integrated Public Use Microdata Series (IPUMS) (1% samples for 1960 and 1970, 5% samples from 1980, 1990 and 2000) as well as the American Community Survey from 2009, we show how a narrow focus on gender oversimplifies the racial and increasingly global dynamics of the scientific labor force. We further examine the factors that produce and constrain the scientific labor force sustaining the complex inequality we see when we disaggregate the demographic profiles of two exemplary science fields, Computing and Life Science.